2023
DOI: 10.3390/diabetology4040041
|View full text |Cite
|
Sign up to set email alerts
|

Recent Advances in Psychotherapeutic Treatment and Understanding of Alexithymia in Patients with Obesity and Diabetes Mellitus Type 2

Filip Mustač,
Tin Galijašević,
Eva Podolski
et al.

Abstract: Alexithymia is the inability to describe one’s own feelings and is being increasingly researched. According to contemporary psychodynamic theories, negative emotions cannot be adequately named and externalized, but remain trapped in the body. Recent research shows the connection of alexithymia with numerous somatic diseases. Diabetes mellitus type 2 and obesity represent great challenges in treatment, and the psychological profiles in these diseases are being studied more and more often. Therefore, alexithymia… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…Consequently, this may have repercussions on better diabetes mellitus control. Similarly, in the case of metabolic syndrome, it is expected that better insight and recognition of certain intrapsychic phenomena will positively affect cooperation in the treatment process [75].Camacho-Barcia et al suggested that excessive consumption of energy-dense foods is driven by heightened food reward sensitivity, problems with self-control, or emotional states. Implementing individualspecific psychological strategies is crucial for ensuring and sustaining weight loss.…”
Section: Psychiatry and Treatment Of Metabolic Syndromementioning
confidence: 99%
“…Consequently, this may have repercussions on better diabetes mellitus control. Similarly, in the case of metabolic syndrome, it is expected that better insight and recognition of certain intrapsychic phenomena will positively affect cooperation in the treatment process [75].Camacho-Barcia et al suggested that excessive consumption of energy-dense foods is driven by heightened food reward sensitivity, problems with self-control, or emotional states. Implementing individualspecific psychological strategies is crucial for ensuring and sustaining weight loss.…”
Section: Psychiatry and Treatment Of Metabolic Syndromementioning
confidence: 99%